Limb salvage surgery - Kadam, Dinesh (Medknow Publication & Media Pvt Ltd, 2013)
The threat of lower limb loss is seen commonly in severe crush injury, cancer ablation, diabetes, peripheral vascular disease and neuropathy. The primary goal of limb salvage is to restore and maintain stability and ambulation. Reconstructive strategies differ in each condition such as: Meticulous debridement and early coverage in trauma, replacing lost functional units in cancer ablation, improving vascularity in ischaemic leg and providing stable walking surface for trophic ulcer. The decision to salvage the critically injured limb is multifactorial and should be individualised along with laid down definitive indications. Early cover remains the standard of care, delayed wound coverage not necessarily affect the final outcome. Limb salvage is more cost-effective than amputations in a long run. Limb salvage is the choice of procedure over amputation in 95% of limb sarcoma without affecting the survival. Compound flaps with different tissue components, skeletal reconstruction; tendon transfer/reconstruction helps to restore function. Adjuvant radiation alters tissue characters and calls for modification in reconstructive plan. Neuropathic ulcers are wide and deep often complicated by osteomyelitis. Free flap reconstruction aids in faster healing and provides superior surface for offloading. Diabetic wounds are primarily due to neuropathy and leads to six-fold increase in ulcerations. Control of infections, aggressive debridement and vascular cover are the mainstay of management. Endovascular procedures are gaining importance and have reduced extent of surgery and increased amputation free survival period. Though the standard approach remains utilising best option in the reconstruction ladder, the recent trend shows running down the ladder of reconstruction with newer reliable local flaps and negative wound pressure therapy.